2016
DOI: 10.48550/arxiv.1607.03611
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterizing Driving Styles with Deep Learning

Abstract: Characterizing driving styles of human drivers using vehicle sensor data, e.g., GPS, is an interesting research problem and an important real-world requirement from automotive industries. A good representation of driving features can be highly valuable for autonomous driving, auto insurance, and many other application scenarios. However, traditional methods mainly rely on handcrafted features, which limit machine learning algorithms to achieve a better performance. In this paper, we propose a novel deep learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 20 publications
(29 reference statements)
0
33
0
Order By: Relevance
“…Deep neural networks have been gaining attention from both academia and industry to deal with GPS trajectory data for prediction tasks such as vehicle or trajectory classification [25], [26], travel prediction [27], [28], [29], and characterizing driving styles [30]. For trajectory data of vehicle movement, although some research suggests that extracting semantic and statistical features can improve the performance (e.g., the accuracy of detection and ROC, etc.)…”
Section: Previous Workmentioning
confidence: 99%
“…Deep neural networks have been gaining attention from both academia and industry to deal with GPS trajectory data for prediction tasks such as vehicle or trajectory classification [25], [26], travel prediction [27], [28], [29], and characterizing driving styles [30]. For trajectory data of vehicle movement, although some research suggests that extracting semantic and statistical features can improve the performance (e.g., the accuracy of detection and ROC, etc.)…”
Section: Previous Workmentioning
confidence: 99%
“…A trip (i.e., GPS trajectory) can be defined by a variedlength sequence of tuples (u, v, t), where (u, v) denotes a geo-location and t denotes time. We follow the data transformation method proposed by [Dong et al, 2016]…”
Section: Gps Data Transformationmentioning
confidence: 99%
“…Trip features are computed using the proposed trip2vec framework for all the nets. We also include a 57-d handcrafted trip feature representation proposed by [Dong et al, 2016] as another baseline, which demonstrated good classification performance working with GBDT (Gradient Boosting Decision Tree) [Friedman, 2001]. We denote it by TripGBDT feature.…”
Section: Experimental Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, knowledge of latent driver styles in surrounding vehicles can improve safety in planning for freeway driving [13]. Prior work in latent state inference in driving contexts has employed a broad range of techniques such as fuzzy logic, hidden Markov models, clustering, and deep learning [14]- [17]. However, these approaches require assumptions about the number or meaning of latent states that may not prove to be valid on naturalistic driving datasets.…”
Section: Introductionmentioning
confidence: 99%